Metabolomic Profile of Salicornia perennis Plant’s Organs under Diverse In Situ Stress: The Ria de Aveiro Salt Marshes Case - Natasha N. Magni; Ana C. S. Veríssimo; Helena Silva; Diana C. G. A. Pinto (Metabolites, 2023)
Salicornia perennis is a halophyte belonging to the botanical subfamily Salicornioideae that forms extensive perennial salt marsh patches. This subfamily has excellent potential, still unexplored, as a source of food, medicine, and phytoremediation. This study aimed to evaluate the lipophilic composition of the Salicornia perennis different organs inhabiting salt marshes of Ria de Aveiro under different stress regimes. For this purpose, the lipophilic content was extracted with hexane and subsequent GC-MS analysis of the extracts for each plant organ, which was collected in three different salt marshes of the Ria de Aveiro. High sugar content was detected in the stems, whereas in fruiting articles, the higher content was in fatty acids. Shorter-chain organic acids were concentrated in the stems and vegetative articles; waxes were detected in greater quantity in photosynthetic organs. More or less stressful environments induce changes in the ratio and composition of molecules, such as acclimatization and oxidative stress reduction strategies; for example, fatty acid content was higher in plants subjected to a higher stress regime. These data contribute to understand the metabolic pathways of the species under study, suggesting new research approaches to its potential as food, medicine, and phytoremediator.